P.039 mTOR inhibitors as a new therapeutic strategy in treatment resistant epilepsy in hemimegalencephaly: a case report. (2nd June 2017) - Xu, Q; Sarnat, H; Uliel-Sibony, S; Boelman, C; Connolly, M; Datta, A
Abstract : Background: Hemimegalencephaly (HME) is a hamartomatous malformation of one cerebral hemisphere, resulting in refractory epilepsy, intellectual disability, and autistic features. Hemispherectomy is the definitive treatment, but there is risk of high morbidity and mortality, especially when done in early infancy. Various preclinical studies have shown that dysregulation of the mTOR pathway has an integral role in the development of various epilepsy syndromes, including tuberous sclerosis complex (TSC), focal cortical dysplasia and HME. Recently, mTOR inhibitors were proven to be effective in treating seizures in TSC.Methods: We present a case of a 6 day old female with refractory epilepsy despite the trial of 9 anti-seizure medications and the ketogenic diet. As the patient was awaiting epilepsy surgery, an mTOR inhibitor, rapamycin was initiated.Results: After 1 week of the initiation, she had over a 50% reduction in seizures. At two weeks, the parents felt that for the first time, she was making developmental gains. She also appeared brighter and more interactive. Due to her response to treatment, her hemispherectomy was deferred to when she is older, so there will be a decreased risk of complications from the surgery.Conclusions: This case exemplifies how mTOR inhibitors should be considered as a treatment option for patients with HME and refractory epilepsy.